The Culture of Opera Buffa in Mozart's Vienna : A Poetics of Entertainment - Hunter, Mary Kathleen, 1951- (Book collections on Project MUSE., 1999)
Mozart's comic operas are among the masterworks of Western civilization, and yet the musical environment in which Mozart and his librettist Lorenzo da Ponte wrote these now-popular operas has received little critical attention. In this book, Mary Hunter offers a sweeping, synthetic view of opera buffa in the lively theatrical world of late-eighteenth century Vienna. Opera buffa (Italian-language comic opera) persistently entertained audiences at a time when Joseph II was striving for a German national theater. Hunter attributes opera buffa's success to the "sheer" pleasure it can provide, and hence explores how the genre functioned as entertainment. She argues that opera buffa, like mainstream film today, projects a social world both recognizable and distinct from reality. It raises important issues while containing them in the "merely entertaining" frame of the occasion, as well as presenting them as a series of easily identifiable dramatic and musical conventions